Coral community structure of Talim Bay, Lian Batangas Philippines - España, Norievill B. (Marine Science Institute, College of Science, University of the Philippines Diliman, 2013)
Patterns in coral community structure exhibited preference of coral communities to either one of the zones in the reef. In Talim Bay, Lian, Batangas, the lagoon is dominated by dome-shape Porities, Pavona frondifera, and P. decussata. The shallow reef flat zones were dominated by encrusting and foliose Montipora, branching and tabulate Acropora as well as dome-shape Porites.The reef crest has higher abundance of corymbose Acropora, dome-shaped Porites and Favites spp. The upper and middle reef slope zones are dominated by Heliopora coerulea, Diploastrea heliopora and dome-shaped Porites. This study continued on to assess whether the coral reef in Talim Bay will be able to bounce back and recover from acute climate-driven disturbances such as an increase in sea surface temperature. Recovery potential was associated with the physical characteristics of the reef, which promoted shading and acclimatization during coral bleaching events; the existing full range of coral size classes (with abundant mid-and large classes of coral colonies); and the presence of adjacent reefs for reseeding and building on the diversity and complexity of the Talim Bay coral reef.